2016
DOI: 10.1111/1745-9133.12195
|View full text |Cite
|
Sign up to set email alerts
|

What Works?

Abstract: Research SummaryWe conducted a meta-analysis of corporate crime deterrence strategies by using 80 effect sizes calculated from 58 studies in four treatment areas-Law, Punitive Sanctions, Regulatory Policy, and Multiple Treatments. Of the single-treatment strategies, only Regulatory Policy produced a significant deterrent impact at the company level, but the results were not consistent across all study and effect size types. Studies examining multiple treatments, though, produced a consistent, significant deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Schell‐Busey et al . 2016). In contrast, the behavioral approach emerged bottom‐up, based on thousands of experimental studies that meticulously mapped various factors that influence behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schell‐Busey et al . 2016). In contrast, the behavioral approach emerged bottom‐up, based on thousands of experimental studies that meticulously mapped various factors that influence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It took time before scholars began examining empirically whether responsive regulation "works," in the sense of increasing compliance (e.g. Schell-Busey et al 2016). In contrast, the behavioral approach emerged bottom-up, based on thousands of experimental studies that meticulously mapped various factors that influence behavior.…”
Section: Behaviorally and Experimentally Informed Responsive Regulationmentioning
confidence: 99%
“…However, as the authors conclude, “with the general weaknesses in the literature, we cannot artfully construct the layers and actions of the enforcement pyramid” (Schell‐Busey et al . 2016). In addition, several interview‐based studies argue that regulators find RR ambiguous and complicated and are often pressured by politicians to take a particular approach toward regulatees, regardless of the pyramid (Mascini & Wijk 2009; Nielsen & Parker 2009).…”
Section: Squaring Regulation and Free Markets: Two Approachesmentioning
confidence: 99%
“…Lynch et al, 2016;Simpson, 2019). Rather than responding with calls for more criminal indictments, fines and prison terms for corporate executives, some legal scholars have argued that the street crimes should be handled more like white-collar crimes, with a variety of deterrence options (Schell-Busey et al, 2016), and that smart policing shown to be effective with street crime could be scaled to address corporate crimes (Brown, 2001;Laufer, 2017). A recent study analyzing the "hot spots" for environmental crime across U.S. states is a promising start in this direction .…”
Section: Cecsmentioning
confidence: 99%